A comprehensive survey on blockchain-based healthcare industry: applications and challenges - Sara Ait Bennacer; Khadija Sabiri; Abdessadek Aaroud; Khalid Akodadi; Bouchaib Cherradi (Institute of Advanced Engineering and Science, 2023)
Blockchain has attracted a lot of interest since its publication because to its unique characteristics of immutability, decentralization, smart contract, and consensus mechanism. Today’s healthcare systems are facing many issues in the era of digital health transformation and the growth of electronic health records. Blockchain has the potential to provide solutions to a variety of electronic health record (EHR)-related challenges, including data management, security, data sharing and patient privacy. This paper represents a blockchain-based healthcare industry survey; it includes many research publications in high-ranking scientific journals in recent years from 2016 to 2022. We adopt the preferred reporting items for systematic reviews and meta-analyses (PRISMA) approach and aspects. This work is based on five databases: Elsevier, Springer, IEEE Xplore, PubMed and MDPI. The number of studies included in this study was 56. We found that researchers attempted to use blockchain technology to assist patients and healthcare providers in diagnosis and data processing, as well as including multiple entities. Our study discusses the potential of blockchain technology, its roles and benefits in healthcare, aiming to solve several problems such as data management, data sharing, access control, data security and privacy, which are missed in the conventional healthcare system.